1
$\begingroup$

The equation

$\dfrac{Y(s)}{s^2} + \dfrac{Y'(s)}{s} = \dfrac{-a}{s^4}$

is in the Laplace transform. How can I take the inverse i.e transform back to time domain and solve for a?

$\endgroup$

2 Answers 2

2
$\begingroup$

$$s Y'(s) +Y(s) = \frac{d}{ds} (s Y(s)) = -\frac{a}{s^2} \implies sY(s) = \frac{a}{s} + C$$

Thus,

$$Y(s) = \frac{a}{s^2} + \frac{C}{s} $$

Inverting the LT, we have

$$y(t) = a t +C$$

Information on $y(0)$ would determine $C$.

$\endgroup$
0
$\begingroup$

I just joined so I can't add a comment to Ron's answer but wanted to clarify that information on y for any t can be used to find C, not just y(0).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.